Etnobotani Tanaman Obat Berbasis Kearifan Lokal Masyarakat di Kecamatan Sungai Mandau Kabupaten Siak Sebagai Rancangan Buku Saku Elektronik Keanekaragaman Hayati - Helmi, Afri; Wulandari, Sri; Darmadi, Darmadi (LPPM Institut Pendidikan Nusantara Global, 2026)
Indonesia is rich in biodiversity, including approximately 35,000 plant species, of which around 7,000 are used as traditional and medicinal remedies. The local wisdom of the community in Sungai Mandau District, Siak Regency, still plays a significant role in utilizing medicinal plants for traditional treatment, especially in areas with limited access to modern healthcare. This research aims to document the ethnobotanical knowledge of medicinal plants in the region and to develop an Electronic Pocket Book as a biology learning resource aligned with the Independent Curriculum. The study used a qualitative survey approach, including interviews and direct observations in five villages. The findings revealed 44 medicinal plant species from 30 families, with Zingiberaceae as the most dominant. The research also included the design and validation of a digital learning media integrating local plant knowledge and biodiversity education. The developed Electronic Pocket Book was deemed valid and suitable for supporting the learning process, especially in identifying local biodiversity and promoting student engagement.